Technical and Financial Feasibility of implementing a photovoltaic system in a private Higher Education Institution in Cajazeiras - PB (Research, Society and Development, 2021)
In a context in which conscious development proves to be more and more necessary, the financial profitability of projects with technological and environmental efficiency is highlighted and is seen as a determining factor for growth. With that in mind, the use of energy originated by the sun, both as a source of heat and light, is conducive to supply all the energy in terms of electricity. Therefore, this research aims to develop a technical economic and financial feasibility study for the implementation of a photovoltaic system in a Private Higher Education Unit in Cajazeiras - PB. For this purpose, this research is a case study, exploratory and descriptive with a quantitative approach. The results showed that the term for the return on investment is 3.8 years and that it is expected that there will be savings of approximately R $ 2,753,000.00 over the next 25 years, which makes the installation of the system quite attractive. Thus, it is evident the benefit that the use of alternative sources can bring both to organizations and to the environment, benefiting the population as a whole. Brazil has enormous potential on the subject, which is solar energy and it can certainly be better explored by all segments of Brazilian / global industry / commerce.